Perancangan Interior Bagi Komunitas Kampoeng Dolanan - Michella Aprilla; Laksmi Kusuma Wardani; M. Taufan Rizqy (Intra, 2018)
Several groups of people was initiating to preserve traditional games and established a community called Kampoeng Dolanan. Kampoeng Dolanan is basically a community that preserves Indonesian traditional games in a unique way (adapting Ki Hajar Dewantara’s teaching method), also encourages people to participate on activities held by the community. However, Kampoeng Dolanan doesn’t have a proper space to facilitate their activities. This design project will provides space to educate, conserve, entertain, and also a place to appreciate traditional games. The design used human-centered design references and focused on community activities with the concept of KML, meaning ‘Introduce, Play, and Preserve’. The design concept is implemented in the space planning and organization, color scheme, material used for the interior elements inside the Omah Dolanan (the name of community’s house). Omah Dolanan itself is organized to accommodate the necessities and activities of the community. Moreover, the purpose of this house is to give people acknowledgement about Indonesian traditional games, also enlighten them about Kampoeng Dolanan at the same time.